2021
DOI: 10.1038/s41575-021-00520-7
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis-associated immune dysfunction

Abstract: In this Review, Albillos and colleagues describe cirrhosis-associated immune dysfunction (CAID) and its components, systemic inflammation and immune deficiency, as well as the role of CAID in the pathogenesis of acute-on-chronic liver failure. Therapies that aim to modulate CAID are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
164
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 253 publications
4
164
0
7
Order By: Relevance
“…Such comparisons between compensated and decompensated patients substantiate that CAID evolves in parallel with liver disease progression ( 1 , 7 , 52 ), with an augmented immune response observed in the decompensated versus compensated patients. This may, in part, be due to the increased expression of pathogen recognition receptors, including TLRs, seen in cirrhotic patients with ascites ( 32 , 53 , 54 ).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Such comparisons between compensated and decompensated patients substantiate that CAID evolves in parallel with liver disease progression ( 1 , 7 , 52 ), with an augmented immune response observed in the decompensated versus compensated patients. This may, in part, be due to the increased expression of pathogen recognition receptors, including TLRs, seen in cirrhotic patients with ascites ( 32 , 53 , 54 ).…”
Section: Discussionmentioning
confidence: 56%
“…Cirrhosis-associated immune dysfunction (CAID) describes the wide array of abnormalities observed in the immune system of cirrhotic patients. It encompasses both overt systemic inflammation and acquired immunodeficiency with impaired response to pathogens ( 1 ). CAID plays a pivotal role in the development of disease progression, acute-on-chronic liver failure (ACLF), and organ failure and increases the propensity to infection ( 1 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver-derived complement proteins form a necessary component of host defense, as evidenced by recurrent infections in patients with cirrhosis ( 9, 40 ). To that effect, we found that splenic dissemination of bacteria was significantly higher in the mice deficient in liver-derived C3 compared to controls, suggesting its role in enhancing immune resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, genetic and acquired deficiencies of complement characteristically lead to recurrent bacterial infections in both children and adults ( 8, 9 ). However, there has been an increasing appreciation recently of how the system functions to promote tissue resilience in the setting of acute infections ( 10, 11 ).…”
Section: Introductionmentioning
confidence: 99%